A HUMAN IN THE URBAN SPACE OF THE GLOBALIZED WORLD - I. O. Merylova; K. V. Sokolova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of the research is to define certain interaction features between a human and the urban environment in the global world. Theoretical basis. The study in based on the investigations of contemporary researchers in social philosophy and urban science, as well as social scientists of Chicago School. Originality. The originality of the research is to analyze the "human-urban space" system in terms of the influence of local space of the global world on the human identity formation and preservation. Conclusions. Modern information technologies have significantly contributed into changes in the culture, society, individual consciousness and perception. They have given them absolutely global character and reorganized the value and standard system of the individual. As a result, it caused the identity crisis, so typical of the postindustrial society. Thus, one of the possible ways to overcome the crisis is to harmonize the interaction in the "human-urban space" system as an area of individual space of human social and cultural identity.